Archives des greffes des tribunaux (principalement ceux de Saint-Domingue) - https://empreintedigitale.fr, Empreinte Digitale / Ligeo-Archives- (Archives nationales d'outre-mer, 1686)
Cet espace vous offre une vue générale des fonds conservés aux Archives nationales d'outre-mer. Il liste les inventaires en ligne ou disponibles sous...

Trans-Atlantic Slave Trade - Database

SlaveVoyages
The SlaveVoyages website offers records about the origins and forced transportation of more than twelve million Africans across the Atlantic and within the Americas. This ever-evolving website is the collaborative effort of dozens of researchers working in libraries and archives around the world. The work of several prominent historians, including Herbert S. Klein, David Richardson, David Eltis, and Stephen Behrendt, was foundational to the creation and expansion of the database over a period of decades. In 2008, the Trans-Atlantic Slave Trade Database was first made freely available online, thanks to the efforts of David Eltis in collaboration with a multidisciplinary and international team of scholars, programmers, librarians, and designers. The database has been repeatedly refreshed and expanded to reflect new research findings and the user interface was modernized from 2015-2018.
Keywords: _open access